2022
DOI: 10.1093/hmg/ddac182
|View full text |Cite
|
Sign up to set email alerts
|

De novovariants cause complex symptoms in HSP-ATL1(SPG3A) and uncover genotype–phenotype correlations

Abstract: Pathogenic variants in ATL1 are a known cause of autosomal-dominantly inherited hereditary spastic paraplegia (HSP-ATL1, SPG3A) with a predominantly ‘pure’ HSP phenotype. Although a relatively large number of patients have been reported, no genotype–phenotype correlations have been established for specific ATL1 variants. Confronted with five children carrying de novo ATL1 variants showing early, complex and severe symptoms, we systematically investigated the molecular and phenotypic spectrum of HSP-ATL1. Throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…The difference in the frequency of exon 1 involvement may explain the discrepancy between our and other studies. Interestingly, we observed that rearrangement‐related SPG3A patients had onset after puberty (33.60 ± 11.28 years), seemingly inconsistent with the common sense that SPG3A is almost exclusively early onset 37‐39 . A reanalysis of 51 reported studies showed that 84.79% SPG3A patients exhibited early AAO (<10 years), whereas 15.21% SPG3A patients had a later AAO (>10 years), and no significant difference was found among different mutation types (missense and small insertion/deletion) 40 .…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The difference in the frequency of exon 1 involvement may explain the discrepancy between our and other studies. Interestingly, we observed that rearrangement‐related SPG3A patients had onset after puberty (33.60 ± 11.28 years), seemingly inconsistent with the common sense that SPG3A is almost exclusively early onset 37‐39 . A reanalysis of 51 reported studies showed that 84.79% SPG3A patients exhibited early AAO (<10 years), whereas 15.21% SPG3A patients had a later AAO (>10 years), and no significant difference was found among different mutation types (missense and small insertion/deletion) 40 .…”
Section: Discussioncontrasting
confidence: 69%
“…Interestingly, we observed that rearrangement-related SPG3A patients had onset after puberty (33.60 AE 11.28 years), seemingly inconsistent with the common sense that SPG3A is almost exclusively early onset. [37][38][39] A reanalysis of 51 reported studies showed that 84.79% SPG3A patients exhibited early AAO (<10 years), whereas 15.21% SPG3A patients had a later AAO (>10 years), and no significant difference was found among different mutation types (missense and small insertion/deletion). 40 Whether rearrangement mutations correlate with late onset and the underlying mechanisms necessitates further studies.…”
mentioning
confidence: 99%
“…The case presented by Damásio et al highlights the important notion that atypical symptoms, including ataxia and other cerebellar signs, can precede pyramidal signs in children with complex HSP. This has been noted in multiple cases and cohorts of autosomal dominant 2,3 and recessive forms, 4,5 and it underscores the phenotypic pleiotropy seen in HSP. These findings demonstrate the importance of careful phenotyping through longitudinal natural history studies.…”
Section: Case Sex Age De Novo Spast Variant a Age At Molecular Diagn...mentioning
confidence: 58%
“…Our findings highlight the important role of comprehensive phenotyping when evaluating potential biomarkers and the need to include matched controls, particularly in the pediatric age group. The former is particularly relevant for neurological disorders with profound phenotypic pleiotropy, such as HSP 25‐28 . Our study provides a data set that adds to the few available data for pNfL in neurologically healthy children 29‐33 .…”
Section: Discussionmentioning
confidence: 94%
“…The former is particularly relevant for neurological disorders with profound phenotypic pleiotropy, such as HSP. [25][26][27][28] Our study provides a data set that adds to the few available data for pNfL in neurologically healthy children. [29][30][31][32][33] In summary, by establishing a baseline of elevated pNfL levels in patients with AP-4-HSP, this first crosssectional study provides the basis for future longitudinal measurement of pNfL, which will help determine whether pNfL is a prognostic biomarker sensitive to disease progression and disease modifying intervention.…”
Section: Discussionmentioning
confidence: 99%